High‐frequency monitoring of catchment nutrient exports reveals highly variable storm event responses and dynamic source zone activation. Issue 9 (7th September 2017) - Blaen, Phillip J.; Khamis, Kieran; Lloyd, Charlotte; Comer‐Warner, Sophie; Ciocca, Francesco; Thomas, Rick M.; MacKenzie, A. Rob; Krause, Stefan
Abstract: Storm events can drive highly variable behavior in catchment nutrient and water fluxes, yet short‐term event dynamics are frequently missed by low‐resolution sampling regimes. In addition, nutrient source zone contributions can vary significantly within and between storm events. Our inability to identify and characterize time‐dynamic source zone contributions severely hampers the adequate design of land use management practices in order to control nutrient exports from agricultural landscapes. Here we utilize an 8 month high‐frequency (hourly) time series of streamflow, nitrate (NO3 ‐N), dissolved organic carbon (DOC), and hydroclimatic variables for a headwater agricultural catchment. We identified 29 distinct storm events across the monitoring period. These events represented 31% of the time series and contributed disproportionately to nutrient loads (42% of NO3 ‐N and 43% of DOC) relative to their duration. Regression analysis identified a small subset of hydroclimatological variables (notably precipitation intensity and antecedent conditions) as key drivers of nutrient dynamics during storm events. Hysteresis analysis of nutrient concentration‐discharge relationships highlighted the dynamic activation of discrete NO3 ‐N and DOC source zones, which varied on an event‐specific basis. Our results highlight the benefits of high‐frequency in situ monitoring for characterizing short‐term nutrient fluxes and unraveling connections between hydroclimatological variability and river nutrient export and source zone activation under extreme flow conditions. These new process‐based insights, which we summarize in a conceptual model, are fundamental to underpinning targeted management measures to reduce nutrient loading of surface waters. Key Points: High‐frequency river monitoring using in situ sensors reveals variability in nutrient dynamics between and during storm events Nutrient dynamics during storm events are predicted by hydroclimatological variables and antecedent conditions Conceptual model of controls on nutrient‐specific source zone activation presented to explain patterns of catchment nutrient export